Multispecies-targeting siRNAs for the modulation of JAK1 in the skin - Qi Tang; Katherine Y. Gross; Hassan H. Fakih; Samuel O. Jackson; Mohammad Zain U.I. Abideen; Kathryn R. Monopoli; Carine Blanchard; Claire Bouix-Peter; Thibaud Portal; John E. Harris; Anastasia Khvorova; Julia F. Alterman (Elsevier, 2024)
Identifying therapeutic oligonucleotides that are cross-reactive to experimental animal species can dramatically accelerate the process of preclinical development and clinical translation. Here, we identify fully chemically-modified small interfering RNAs (siRNAs) that are cross-reactive to Janus kinase 1 (JAK1) in humans and a large variety of other species. We validated the identified siRNAs in silencing JAK1 in cell lines and skin tissues of multiple species. JAK1 is one of the four members of the JAK family of tyrosine kinases that mediate the signaling transduction of many inflammatory cytokine pathways. Dysregulation of these pathways is often involved in the pathogenesis of various immune disorders, and modulation of JAK family enzymes is an effective strategy in the clinic. Thus, this work may open up unprecedented opportunities for evaluating the modulation of JAK1 in many animal models of human inflammatory skin diseases. Further chemical engineering of the optimized JAK1 siRNAs may expand the utility of these compounds for treating immune disorders in additional tissues.